2004
DOI: 10.1016/j.envpol.2004.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Growth response to ozone of annual species from Mediterranean pastures

Abstract: "Capsule": The therophytes from dehesa acidic pastures of central of the Iberian peninsula present a great sensitivity to ozone, as derived from growth-and biomass-r elated variables.Abstract Ozone (0 3 ) phytotoxicity has been reported on a wide range of plant species. However, scarce information has been provided regarding the sensitivity of semi-natural grassland species, especially those from dehesa Mediterranean grasslands, in spite of their great biological diversity and the high 0 3 levels recorded in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…In temperate grasslands, experimental O 3 treatment reduced seed number, fruit number, and weight, but increased flower number and flower weight in a number of species, for example, in paper birch ( Betula papyrifera ) (Leisner & Ainsworth, 2012), and decreased seed weight and germination rate (Darbah et al., 2008) with implications for the establishment and survival of the progeny. Where plant composition greatly depends on the belowground seed pool, declining reproductive success can be caused by elevated O 3 exposure, such as in the Dehesa annual grasslands, which cover several million hectares in the Iberian Peninsula within the highly O 3 ‐exposed “Mediterranean forests, woodlands, and shrubs” ER (Table 1; Gimeno, Bermejo, Sanz, De La Torre, & Elvira, 2004). …”
Section: Changes In Plant Communitiesmentioning
confidence: 99%
“…In temperate grasslands, experimental O 3 treatment reduced seed number, fruit number, and weight, but increased flower number and flower weight in a number of species, for example, in paper birch ( Betula papyrifera ) (Leisner & Ainsworth, 2012), and decreased seed weight and germination rate (Darbah et al., 2008) with implications for the establishment and survival of the progeny. Where plant composition greatly depends on the belowground seed pool, declining reproductive success can be caused by elevated O 3 exposure, such as in the Dehesa annual grasslands, which cover several million hectares in the Iberian Peninsula within the highly O 3 ‐exposed “Mediterranean forests, woodlands, and shrubs” ER (Table 1; Gimeno, Bermejo, Sanz, De La Torre, & Elvira, 2004). …”
Section: Changes In Plant Communitiesmentioning
confidence: 99%
“…Gimeno et al (2004a) indicated that, under high O3 levels, 70% of the assayed legume species experienced a reduction in their relative growth; meanwhile, 75% of the studied grasses showed no effect in terms of growth. These heterogeneous responses among species can potentially alter the structure and composition of the pastures in areas under chronic O3 pollution, although no studies up to the present work have been done that consider the O3 effects at community scale.…”
Section: Effects On Growth and Biomass Productionmentioning
confidence: 93%
“…Since the last decade, significant effort is ongoing for assessing the O3 responses of annual species belonging to these Mediterranean pastures. Ozone has been recognized as an important negative factor causing foliar damage and affecting their growth, yield, consumable food value and reproductive capacity (Bermejo et al, 2003;Gimeno et al, 2004a;Sanz et al, 2005Sanz et al, , 2007Sanz et al, , 2011Sanz et al, , 2014. To investigate the pollutant effects on pasture, these studies employed…”
Section: Ozone Effects On Therophytic Pasturesmentioning
confidence: 99%
See 2 more Smart Citations